Experimental investigation of thermal modification influence on sorption qualities of biosorbents - Pranas Baltrenas (Journal of Environmental Engineering and Landscape Management, 2005)
When collecting oil products from a water surface water soaking is unavoidable. It makes a sorbent sink into water and reduces its capacity to take oil products. Previous experiments have revealed [15] that a biosorbent made of moss growing in Lithuania absorb oil products efficiently from a water surface but water soaking is high (14 g of water / g of a sorbent). To reduce water soaking a biosorbent should be impregnated or modified in another way. Impregnation results in occurrence of certain substances in a sorbent that increase pollution, if the sorbent is left in nature. One of the most perspective ways of modification without extra chemical substances is thermal modification. During heating chemical changes (dissociation of‐COOH and ‐OH free radicals) occur in a biosorbent, which have an influence on the combining of water molecules. A reduced number of these free radicals results in a reduced amount of soaked water. A biosorbent made of moss is very flammable, so definition of a sufficient and safe heating temperature and heating time is very important.